Implementasi Dan Pengujian Sistem Otomatisasi Pengomposan Pupuk Kompos Berbasis Internet Of Things - Mohammad Aprizal; Agus Wagyana (Politeknik Negeri Jakarta, 2025)
The conventional composting process often experiences instability in environmental parameters such as temperature, humidity, and pH, resulting in longer decomposition time and inconsistent compost quality. This study aims to design and develop an Internet of Things (IoT)-based automatic composter system capable of monitoring and controlling critical parameters during the composting process in real time. The system utilizes temperature, humidity, and pH sensors integrated with a microcontroller to automatically activate the heating element and fan according to the required conditions. The process data are transmitted to a website, enabling users to perform remote monitoring. Experimental results show that the system operates stably with sensor accuracy within acceptable tolerance limits, with an error of 3.00% for temperature, 7.88% for pH, and a consistent linear relationship in soil moisture measurements. With the maintained stability of these parameters, the composting process proceeds more quickly and produces more mature and uniform compost. This system offers a practical solution for organic waste management at the household scale.